Comparison of gait speeds from wearable camera and accelerometer in structured and semi‐structured environments. Issue 1 (17th February 2020) - Schneider, Bradley; Banerjee, Tanvi; Grover, Francis; Riley, Michael
Abstract : A feasibility study was conducted to investigate the use of a wearable gait analysis system for classifying gait speed using a low‐cost wearable camera in a semi‐structured indoor setting. Data were collected from 19 participants who wore the system during indoor walk sequences at varying self‐determined speeds (slow, medium, and fast). Gait parameters using this system were compared with parameters obtained from a vest comprising of a single triaxial accelerometer and from a marker‐based optical motion‐capture system. Computer‐vision techniques and signal processing methods were used to generate frequency‐domain gait parameters from each gait‐recording device, and those parameters were analysed to determine the effectiveness of the different measurement systems in discriminating gait speed. Results indicate that the authors' low‐cost, portable, vision‐based system can be effectively used for in‐home gait analysis.